Polygonum cuspidatum and Its Active Components Inhibit Replication of the Influenza Virus through Toll-Like Receptor 9-Induced Interferon Beta Expression - Lin, Chao-jen; Lin, Hui-Ju; Chen, Ter-Hsin; Hsu, Yu-An; Liu, Chin-San; Hwang, Guang-Yuh; Wan, Lei (PloS one, 2015)
Influenza virus infection is a global public health issue. The effectiveness of antiviral therapies for influenza has been limited by the emergence of drug-resistant viral strains. Therefore, there is an urgent need to identify novel antiviral therapies. Here we tested the effects of 300 traditional Chinese medicines on the replication of various influenza virus strains in a lung cell line, A549, using an influenza-specific luciferase reporter assay. Of the traditional medicines tested, Polygonum cuspidatum (PC) and its active components, resveratrol and emodin, were found to attenuate influenza viral replication in A549 cells. Furthermore, they preferentially inhibited the replication of influenza A virus, including clinical strains isolated in 2009 and 2011 in Taiwan and the laboratory strain A/WSN/33 (H1N1). In addition to inhibiting the expression of hemagglutinin and neuraminidase, PC, emodin, and resveratrol also increased the expression of interferon beta (IFN-β) through Toll-like receptor 9 (TLR9). Moreover, the anti-viral activity of IFN-β or resveratrol was reduced when the A549 cells were treated with neutralizing anti-IFN-β antibodies or a TLR9 inhibitor, suggesting that IFN-β likely acts synergistically with resveratrol to inhibit H1N1 replication. This potential antiviral mechanism, involving direct inhibition of virus replication and simultaneous activation of the host immune response, has not been previously described for a single antiviral molecule. In conclusion, our data support the use of PC, resveratrol or emodin for inhibiting influenza virus replication directly and via TLR-9-induced IFN-β production.